Real-World Impact of Surgical Excision on Overall Survival in Primary Central Nervous System Lymphoma - Deng, Xiangyang; Xu, Xingxing; Lin, Dongdong; Zhang, Xiaojia; Yu, Lisheng; Sheng, Hansong; Yin, Bo; Zhang, Nu; Lin, Jian (Frontiers in Oncology, 2020)
Substantial controversy still exists regarding the use of surgical excision in the treatment of primary central nervous system lymphoma (PCNSL). This study was aimed to evaluate survival benefit of surgical excision in PCNSL patients based on U.S. population. Using the Surveillance, Epidemiology, and End Results (SEER) Program database, a total of 3543 PCNSL patients were identified from 2000 to 2014 for analysis. Surgical excision was accessed via Kaplan-Meier and multivariate Cox regression survival analyses. Coarsened Exact Matching (CEM) analysis was additional employed to intensify our findings. Finally, we found surgical excision was significantly associated with increased survival over no surgery/biopsy (P<0.001), and its survival benefit was also independent of baseline prognostic factors. The survival benefit of surgery was also validated in clinically important subsets. CEM analysis further validated the survival advantage of surgery (P<0.001). Moreover, a novel prediction model with excellent performance was established to estimate the potential beneﬁt from surgical excision of the lesion with respect to the end point of overall survival. The current study supports the favorable impact of surgical excision on clinical outcome in patients with PCNSL. Although further randomized controlled trials is warrant, currently available evidence should be considered in clinical management of this disease.